Application Of Trial Finalization System As Determinants Of Final Thesis Session Results - Rahardja, Untung; Andayani, Dwi; Aristo, Nabila Cynthia; Hasibuan, Zainal Arifin (Pandawan Sejahtera Indonesia, 2019)
The objective assessment system and guiding assessment can be accessed online, but the examiner's assessment system in which there is a system of finalizing the trial still using the local network and not connected with the others. The trial appraisal system that was not mutually integrated made the examiner a little difficult. This is because as technology advances are utilized as well as possible by educational institutions in this case namely universities to be used in a comprehensive session of thesis students or final assignments. Then it is necessary to develop the examiner's assessment system in which there is a system of finalizing the trial. The research was conducted using the method of observation, interviews and literature studies to maximize this research. The researcher directly examines the congregation assessment system which still uses the local network to analyze how the system works so that when carried out development does not change the existing system flow. Interviews were also conducted by researchers to collect data from existing speakers, namely the board of examiners. Then the author searched the list of previous studies that are appropriate so that repetition does not occur. After the development of the examiner's assessment system along with the finalization of the session and making the system integrated with each other so as to facilitate the examiner chairman to use it in determining whether or not students are declared eligible to pass a comprehensive trial or not. This proved that the system that had been developed greatly helped the process of the trial.